Endothelial Dysfunction, and A Prothrombotic, Proinflammatory Phenotype Is Caused by Loss of Mitochondrial Thioredoxin Reductase in Endothelium. Issue 9 (September 2016) - Kirsch, Julian; Schneider, Holger; Pagel, Judith-Irina; Rehberg, Markus; Singer, Miriam; Hellfritsch, Juliane; Chillo, Omary; Schubert, Kai Michael; Qiu, Jiehua; Pogoda, Kristin; Kameritsch, Petra; Uhl, Bernd; et al.
Abstract : Objective—: Although the investigation on the importance of mitochondria-derived reactive oxygen species (ROS) in endothelial function has been gaining momentum, little is known on the precise role of the individual components involved in the maintenance of a delicate ROS balance. Here we studied the impact of an ongoing dysregulated redox homeostasis by examining the effects of endothelial cell–specific deletion of murine thioredoxin reductase 2 (Txnrd2), a key enzyme of mitochondrial redox control. Approach and Results—: We analyzed the impact of an inducible, endothelial cell–specific deletion of Txnrd2 on vascular remodeling in the adult mouse after femoral artery ligation. Laser Doppler analysis and histology revealed impaired angiogenesis and arteriogenesis. In addition, endothelial loss of Txnrd2 resulted in a prothrombotic, proinflammatory vascular phenotype, manifested as intravascular cellular deposits, as well as microthrombi. This phenotype was confirmed by an increased leukocyte response toward interleukin-1 in the mouse cremaster model. In vitro, we could confirm the attenuated angiogenesis measured in vivo, which was accompanied by increased ROS and an impaired mitochondrial membrane potential. Ex vivo analysis of femoral arteries revealed reduced flow-dependent vasodilation in endothelial cell Txnrd2-deficient mice. This endothelial dysfunction could be, at least partly, ascribed to inadequate nitric oxide signaling. Conclusions—: We conclude that the maintenance of mitochondrial ROS via Txnrd2 in endothelial cells is necessary for an intact vascular homeostasis and remodeling and that Txnrd2 plays a vitally important role in balancing mitochondrial ROS production in the endothelium. Abstract : Supplemental Digital Content is available in the text.